New insights into the dust formation of oxygen-rich AGB stars - Karovicova, Iva; Wittkowski, M.; Ohnaka, K.; Boboltz, D. A.; Fossat, E.; Scholz, Michael (Astronomy and astrophysics, 2013)
Context. Asymptotic giant branch (AGB) stars are one of the major sources of dust in the universe. The formation of molecules and dust grains and their subsequent expulsion into the interstellar medium via strong stellar winds is under intense investigation. This is in particular true for oxygen-rich stars, for which the path of dust formation has remained unclear.Aims. We conducted spatially and spectrally resolved mid-infrared multi-epoch interferometric observations to investigate the dust formation process in the extended atmospheres of oxygen-rich AGB stars.Methods. We observed the Mira variable AGB stars S Ori, GX Mon, and R Cnc between February 2006 and March 2009 with the MIDI instrument at the VLT interferometer. We compared the data to radiative transfer models of the dust shells, where the central stellar intensity profiles were described by dust-free dynamic model atmospheres. We used Al2O3 and warm silicate grains, following earlier studies in the literature.Results. Our S Ori and R Cnc data could be well described by an Al2O3 dust shell alone, and our GX Mon data by a mix of an Al2O3 and a silicate shell. The best-fit parameters for S Ori and R Cnc included photospheric angular diameters ΘPhot of 9.7 ± 1.0 mas and 12.3 ± 1.0 mas, optical depths τV(Al2O3) of 1.5 ± 0.5 and 1.35 ± 0.2, and inner radii Rin of 1.9 ± 0.3 RPhot and 2.2 ± 0.3 RPhot, respectively. Best-fit parameters for GX Mon were ΘPhot = 8.7 ± 1.3 mas, τV(Al2O3) = 1.9 ± 0.6, Rin(Al2O3) = 2.1 ± 0.3 RPhot, τV(silicate)= 3.2 ± 0.5, and Rin(silicate)= 4.6 ± 0.2 RPhot. Our data did not show evidence of intra-cycle and cycle-to-cycle variability or of asymmetries within the error-bars and within the limits of our baseline and phase coverage. Conclusions. Our model fits constrain the chemical composition and the inner boundary radii of the dust shells, as well as the photospheric angular diameters. Our interferometric results are consistent with Al2O3 grains condensing close to the stellar surface at about 2 stellar radii, co-located with the extended atmosphere and SiO maser emission, and warm silicate grains at larger distances of about 4-5 stellar radii. We verified that the number densities of aluminum can match that of the best-fit Al2O3 dust shell near the inner dust radius in sufficiently extended atmospheres, confirming that Al2O3 grains can be seed particles for the further dust condensation. Together with literature data of the mass-loss rates, our sample is consistent with a hypothesis that stars with low mass-loss rates form primarily dust that preserves the spectral properties of Al2O3, and stars with higher mass-loss rate form dust with properties of warm silicates.